Ba1.2-xCsxM1.2-x/2Ti6.8+x/2O16 (M = Ni, Zn) hollandites for the immobilisation of radiocaesium. (2020) - Bailey, D. J.; Stennett, M. C.; Hyatt, N. C.
ABSTRACT: Improved budgeting of heat loads arising from radiogenic heating in high level wastes (HLW) could allow enhanced usage of geological disposal facility space. Separation of high heat generating nuclides from HLW, such as Cs, would simplify management of heat loads. A potential host matrix for Cs-disposal is hollandite. The incorporation of Cs into the hollandite phase is aided by substitution of cations on the B-site of the structure; these ions may include Ni and Zn. Two series of hollandites, Ni-substituted and Zn-substituted, were synthesised via an alkoxide-nitrate route and consolidated by cold uniaxial pressing and sintering or by hot isostatic pressing. Characterisation of the resultant material by X-ray diffraction and scanning electron microscopy found that hollandite was formed for all levels of substitution. Materials produced via HIP were found to be denser indicating lower Cs loss. HIPed Ni hollandites were found to contain fewer secondary phases and it was concluded that they were the most suitable candidates